Pengaruh Digitalisasi Bisnis Terhadap Penignkatan Pendapatan UMKM di Dikota Gorontalo (Studi Kasus UMKM Sektor Pangan) - Ahmad, Moh. Hariadi; Olilingo, Fahrudin Zain; Santoso, Ivan Rahmad (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to determine the effect of business digitalization on increasing the revenue of Micro, Small, and Medium Enterprises (MSMEs) in the food sector in Gorontalo City. Business digitalization in this study is measured through two main indicators: e-commerce utilization and the use of the QRIS digital payment system. The research method used is quantitative research using multiple linear regression analysis. Primary data was obtained through questionnaires distributed to 100 respondents from the food sector MSMEs across Gorontalo City. The results indicate that business digitalization has a positive and significant impact on increasing MSME revenue in Gorontalo City. Simultaneously, the E-commerce and QRIS variables have a significant effect on income with a significance value of 0.000 or 0.00%. Partially, the use of E-commerce has a significant effect with a significance value of 0.004 or 0.4%, while QRIS also has a significant effect with a significance value of 0.000 or 0.00%. The coefficient of determination (R²) value of 0.341 indicates that 34.1% of the variation in income increase is explained by business digitalization, while the rest is influenced by other factors outside the research model.